Is Speed a Desirable Difficulty for Learning Procedures? An Initial Exploration of the Effects of Chronometric Pressure. (June 2018) - Gas, Becca L.; Buckarma, EeeLN H.; Cook, David A.; Farley, David R.; Pusic, Martin V.
Abstract : Purpose: To determine whether "chronometric pressure" (i.e., a verbal prompt to increase speed) could predictably alter medical learners' speed–accuracy trade-off during a simulated surgical task, thus modifying the challenge. Method: The authors performed a single-task, interrupted time-series study, enrolling surgery residents and medical students from two institutions in September and October 2015. Participants completed 10 repetitions of a simulated blood vessel ligation (placement of two ligatures 1 cm apart). Between repetitions 5 and 6, participants were verbally encouraged to complete the next repetition 20% faster than the previous one. Outcomes included time and accuracy (ligature tightness, placement distance). Data were analyzed using random-coefficients spline models. Results: The authors analyzed data from 78 participants (25 medical students, 16 first-year residents, 37 senior [second-year or higher] residents). Overall, time decreased from the 1st (mean [standard deviation] 39.8 seconds [18.4]) to the 10th (29.6 [12.5]) repetition. The spline model showed a decrease in time between repetitions 5 and 6 of 8.6 seconds (95% confidence interval: −11.1, −6.1). The faster time corresponded with declines in ligature tightness (unadjusted difference −19%; decrease in odds 0.86 [0.76, 0.98]) and placement accuracy (unadjusted difference −5%; decrease in odds 0.86 [0.75, 0.99]). Significant differences in the speed–accuracy trade-off were seen by training level, with senior residents demonstrating the greatest decline in accuracy as speed increased. Conclusions: Chronometric pressure influenced the speed–accuracy trade-off and modified the challenge level in a simulated surgical task. It may help unmask correctable deficiencies or false plateaus in learners' skill development. Abstract : Supplemental Digital Content is available in the text.